2018
DOI: 10.5430/ijba.v9n5p21
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cognitive Factors on Self-Employment Intention Among Students in Technical, Vocational Education and Training in Kenya

Abstract: Entrepreneurship has been identified as a crucial activity for economic growth and employment generation worldwide. However, this has not been effective in most developing countries, Kenya as an example, has a high rate of unemployment among the young graduates emerging from universities and tertiary institutions. One of the government challenges is transforming the mindset of students to venture into business rather than seeking employments. This study thus examined the relationship between cognitive factors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…One of the core guiding principles of Kenyan higher education as enshrined in section 4.r of the policy, is the "promotion of … an entrepreneurial culture" (Kenya 2013:226), prompting the incorporation of "entrepreneurial education … into undergraduate courses in universities, colleges and tertiary institutions" (Mwanzu & Wendo 2021:6). Kahando and Mungai (2018) earlier found that this strategy is effective even amongst students in different academic background: "the introduction of entrepreneurship education as a compulsory course among engineering students … strongly influenced [their] self-employment intention … in Kenya" (Kahando & Mungai 2018:30). Nigeria's journey with compulsory entrepreneurship pedagogy, on the other hand, began since 2006 when "Government decided to introduce … Entrepreneurship Module into the curriculum of all universities" (Meng et al 2019:1).…”
Section: Discussion: Towards Hep 101's First Didactic Amendment?mentioning
confidence: 99%
“…One of the core guiding principles of Kenyan higher education as enshrined in section 4.r of the policy, is the "promotion of … an entrepreneurial culture" (Kenya 2013:226), prompting the incorporation of "entrepreneurial education … into undergraduate courses in universities, colleges and tertiary institutions" (Mwanzu & Wendo 2021:6). Kahando and Mungai (2018) earlier found that this strategy is effective even amongst students in different academic background: "the introduction of entrepreneurship education as a compulsory course among engineering students … strongly influenced [their] self-employment intention … in Kenya" (Kahando & Mungai 2018:30). Nigeria's journey with compulsory entrepreneurship pedagogy, on the other hand, began since 2006 when "Government decided to introduce … Entrepreneurship Module into the curriculum of all universities" (Meng et al 2019:1).…”
Section: Discussion: Towards Hep 101's First Didactic Amendment?mentioning
confidence: 99%
“…Self-efficacy, self-enthusiasm, and commitment (Kahando & Mungai, 2018) -Bearing risks, creativity, and innovative ideas (Halvorsen and Morrow-Howell, 2017) 'Working for oneself' (p.314). Self-employers are considered social entrepreneurs, entrepreneurs, small company owners, and consultants.…”
Section: Citementioning
confidence: 99%